Exploring future research and innovation directions for a sustainable blue economy. (February 2023) - Pace, Lisa A.; Saritas, Ozcan; Deidun, Alan
Abstract: The blue economy integrates commercial, research and innovation activities across diverse industrial sectors. Achieving a sustainable blue economy requires unlocking the potential of science and innovation to develop innovative ocean sustainability solutions. This study explores the role of foresight in co-creating alternative, preferred futures for a sustainable blue economy looking towards 2030 and in establishing an interdisciplinary dialogue about research and innovation opportunities to achieve these futures. To this end, a foresight exercise is conducted with marine scientists and researchers in 6 countries in Europe. The exercise is designed in three stages: scanning, scenario-building and strategic orientation, and uses a combination of foresight methods to encourage creative thinking and exploration. The scenarios developed in the study describe alternative future worlds built on the establishment of self-sustaining communities and engaged societies; the diffusion of digitalisation and growth of blue biotechnologies; booming ecosystem services and open and collaborative research infrastructures that impact different sectors of the blue economy. A portfolio of research and innovation areas is developed that aims to inspire new research directions in four domains: (i) integrated ocean management tools; (ii) closed loop, circular polyculture systems; (iii) co-creation of innovation and transdisciplinary research; and (iv) open access and collaborative databases supporting ecosystem services. The study highlights the role of foresight in bridging across disciplinary perspectives and industry sectors. Foresight can be used to complement Decision-Support Systems and other quantitative approaches for research agenda-setting and for decision-making on policies addressing sustainability in the marine sciences. The process contributes to futures skills-building at institutional level and helps establish a futures mindset for strategic planning. Highlights: Alternative future scenarios are co-created for a sustainable blue economy. A portfolio of future research and innovation directions is presented. Participatory approaches facilitate a futures dialogue in an interdisciplinary context. Foresight can be used alongside Decision Support Systems in sustainability science.